Human Capital as Enabler of Career Success: Perceptions of Nepali Women Executives - Adhikary, Jyoti Regmi; Shrestha, Binod Krishna (Journal of Business and Management Research, 2023)
This study explored the perceptions of Nepali women executives about human capital elements that enabled their career success. In-depth interviews were used to generate information from purposively selected ten women executives representing varied organizations. Analysis revealed six human capital enablers to contribute to their career success: education, experience, expertise, performance, training, and relevant knowledge. Results show that human capital enables career success both directly and indirectly. The study outlines the pathway of career success and highlights the importance of socio-cultural consideration in further research in Nepal.